APPLYING DICTOGLOSS TECHNIQUE TO IMPROVE STUDENTS’ LISTENING ABILITY OF SHORT STORY: AN EXPERIMENTAL STUDY AT A JUNIOR HIGH SCHOOL IN PEKANBARU - Kurniawan, Robi; Meutia (Indonesian Journal of Studies on Humanities, Social Sciences and Education, 2025)
This study aims to identify the significant effect on the use of Dictogloss Technique on listening ability to short story in the second grade of Junior High School 20 Pekanbaru. In this quantitative research, the design used pre-experiment with only one class pre-test and post-test. The population of this research was second grade students at Junior High School 20 Pekanbaru. The researcher used simple random sampling technique in which class VIII.8 of Junior High School became the research sample which amounted to 34 students. Researcher used objective tests as a data collection technique. Then the researcher tested the data with T-test and obtained data 1.692, then T-Table -1.507 and Sig. (2 tailed) is 0.000 less than 0.05. Then H0 is rejected and Ha is accepted. In conclusion, there is a significant effect on the use of Dictogloss Technique on listening ability to short story of students in the second grade of Junior High School 20 Pekanbaru.